1992
DOI: 10.1016/0040-6090(92)90207-r
|View full text |Cite
|
Sign up to set email alerts
|

Mixed polymeric monolayers and Langmuir-Blodgett multilayers with functional low molecular weight guest compounds

Abstract: Mixed monol ayers and Langmuir -Blodgett muItilayers of functional low molecular weight guest compo unds. especially nonlinear optical (N LO) dyes. within the matri x of an ampho tro pic spacer polymer have been prep ared. The polymer matri x enabled the transfer of guest compounds not cap able of self-organizing at the air-water inter face by themselves. The structure of the LB muItilayers and the tran sfer process were studied by sma ll angle X-ray scattering and Uv -visible spectroscopy. Good N LO coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Since the chemical incorporation of dyes into amphiphilic polymers is painstaking and encounters various practical problems, two alternative strategies have been developed. Either the charged amphiphilic dyes are spread on sub-phases containing an oppositely charged polyelectrolyte, forming a polymer complex at the interface [15][16][17][18][19], or amphiphilic dyes are co-spread with polymeric amphiphiles [19,20] analogous to co-spreading with low-molecular-weight amphiphiles. Both strategies provide good results.…”
Section: Introductionmentioning
confidence: 99%
“…Since the chemical incorporation of dyes into amphiphilic polymers is painstaking and encounters various practical problems, two alternative strategies have been developed. Either the charged amphiphilic dyes are spread on sub-phases containing an oppositely charged polyelectrolyte, forming a polymer complex at the interface [15][16][17][18][19], or amphiphilic dyes are co-spread with polymeric amphiphiles [19,20] analogous to co-spreading with low-molecular-weight amphiphiles. Both strategies provide good results.…”
Section: Introductionmentioning
confidence: 99%
“…The reversible photoisomerization characteristics of azobenzene compounds are being considered for a number of molecular electronic devices which include optical memory and optical switching. , The Langmuir−Blodgett (LB) manipulation of azobenzene-functionalized molecules, in particular, allows the study of the cis − trans photoisomerization of the azo functionality in the solid state, especially in the form of ultrathin films whose packing can be controlled at the molecular level. Several molecular engineering approaches have been used for preparing LB films of these compounds, the most common one being the use of long chain amphiphilic azobenzene derivatives that possess amphipatic properties to form stable and easily transferable monolayers. In an earlier study, we have shown that a stable monolayer of methacrylic homopolymer could be obtained in which disperse red-13 dye (DR13) is attached as a pendent group (HPDR13).…”
Section: Introductionmentioning
confidence: 99%